How enhancing information and communication technology has affected inequality in Africa for sustainable development: An empirical investigation - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
This study examines if enhancing ICT reduces inequality in 48 countries in Africa for the period 2004-2014. Three inequality indictors are used, namely, the: Gini coefficient, Atkinson index and Palma ratio. The adopted ICT indicators include: mobile phone penetration, internet penetration and fixed broadband subscriptions. The empirical evidence is based on the Generalised Method of Moments. Enhancing internet penetration and fixed broadband subscriptions have a net effect on reducing the Gini coefficient and the Atkinson index, whereas increasing mobile phone penetration and internet penetration reduces the Palma ratio. Policy implications are discussed in the light of challenges to Sustainable Development Goals.
Keywords: G20; I10; I32; O40; O55; 330; ICT; Inclusive development; Africa; Sustainable development